2018
DOI: 10.1590/s1519-99402018000400003
|View full text |Cite
|
Sign up to set email alerts
|

Productive and economic performance of goats of different genetic groups

Abstract: SUMMARY This study aimed to evaluate the bio-economic performance in confinement crossbred goats from different genetic groups. Were used 30 goats, crossbred (F1) intact male, 10 goats Boer x SPRD (undefined breed), 10 x Savannah SPRD and 10 Oberhasli x SPRD, with an average weight of 15 kg and an average age of 100 days. The initial weight was evaluated, final body weight, average daily gain, total weight gain, dry matter intake, water intake, feed conversion and days on feed. As an economic indicator was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The increasing scarcity of this precious natural resource has drawn concern from different segments of society, who seek solutions for rational and sustainable use of this resource [2]. The meat of small ruminants, such as sheep and goats, is a food source in many parts of the world, and the high adaptability of these animals in semiarid and arid areas allows them to use water efficiently [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing scarcity of this precious natural resource has drawn concern from different segments of society, who seek solutions for rational and sustainable use of this resource [2]. The meat of small ruminants, such as sheep and goats, is a food source in many parts of the world, and the high adaptability of these animals in semiarid and arid areas allows them to use water efficiently [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The current study revealed that ThGr groups was the best regarding the net farm income. Better performance of the animal such as weight gain and FCR will providing higher incomes, total profit margin with reducing production costs 75,76 . El-Azrak et al 77 reported an improvement in the immune response and serum IgG following essential oil supplementation of goats which supported the current results 78 .…”
Section: Discussionmentioning
confidence: 99%